Exploring presenteeism trends: a comprehensive bibliometric and content analysis - Chandrakumar, Divyakala; Arumugam, Vasumathi; Vasudevan, Asokan (Frontiers in Psychology, 2024)
Objective This research will conduct a bibliometric and content analysis of presenteeism from 2000 to 2023. It aims to investigate publication trends, authorship patterns, and significant publications by using presenteeism conceptualizations, measurements, determinants, consequences, and interventions analysis. The study provides valuable insights for researchers, practitioners, and policymakers about understanding and addressing workplace presenteeism issues. Methods The research involved conducting a bibliometric study to analyze presenteeism publication trends, authorship patterns, and significant publications. It also explored the evolution of presenteeism research over time, identifying contributing countries, institutions, and writers. The interdisciplinary nature of presenteeism research was emphasized, covering occupational health, psychology, management, and public health. The researchers have used VOS Viewer and R Studio (biblioshiny) for this study. Results The study identified several elements influencing presenteeism, such as health issues, work-related factors, organizational culture, and individual characteristics. It further examined the impact of organizational policies, leadership support, employee assistance programs, and health promotion activities in reducing absenteeism and enhancing employee well-being. These findings highlight the importance of addressing these factors to mitigate presenteeism issues and promote a healthier work environment. Conclusion This research identified deficiencies in presenteeism research and provided recommendations for future investigations in this field. It emphasized the need for standardized measures and methodologies, longitudinal studies to understand causality, and industry- and population-specific interventions. These insights can guide future research directions and interventions to address presenteeism issues in a rapidly changing work and research landscape.